Molecular genetic analysis of the nested Drosophila melanogaster lamin C gene. - Schulze, S.R.; Curio-Penny, B.; Li, Y.; Imani, R.A.; Rydberg, L.; Geyer, P.K.; Wallrath, L.L. (Genetics, 2005)
Lamins are intermediate filaments that line the inner surface of the nuclear envelope, providing structural support and making contacts with chromatin. There are two types of lamins, A- and B-types, which differ in structure and expression. Drosophila possesses both lamin types, encoded by the LamC (A-type) and lamin Dm0 (B-type) genes. LamC is nested within an intron of the essential gene ttv. We demonstrate that null mutations in LamC are lethal, and expression of a wild-type LamC transgene rescues lethality of LamC but not ttv mutants. Mutations in the human A-type lamin gene lead to diseases called laminopathies. To determine if Drosophila might serve as a useful model to study lamin biology and disease mechanisms, we generated transgenic flies expressing mutant LamC proteins modeled after human disease-causing lamins. These transgenic animals display a nuclear lamin aggregation phenotype remarkably similar to that observed when human mutant A-type lamins are expressed in mammalian cells. LamC aggregates also cause disorganization of lamin Dm0, indicating interdependence of both lamin types for proper lamina assembly. Taken together, these data provide the first detailed genetic analysis of the LamC gene and support using Drosophila as a model to study the role of lamins in disease.